Is the existence of cervical rib an advantage for C7 posterior stabilization? - Ozturk, Sait; Yildirim, Hanefi; Kaplan, Metin (Medknow Publications & Media Pvt Ltd, 2016)
Background and Aim: Defining a new screwing method for C7 posterior stabilization in case of a cervical rib existence aimed in this report. Materials and Methods: Ten adult patients, five of which without cervical rib (Group 1) and the other five of which (Group 2) with cervical rib that has been chosen from the radiology archive. Axial, sagittal, coronal sections of cervical computed tomography and three-dimensional images were obtained. Lateral mass sizes of all cases were measured and compared between two groups. The relationship between cervical rib and lateral mass was identified in Group 2. Results: The mean length, width, and height of lateral masses were measured respectively, as 5.4, 17.6, and 12.7 mm in Group 1. The measurement of Group 2 (with cervical rib) revealed the mean length of 20.7, the width of 20.4, and the height of 15.9 mm. When both groups were compared, there were no significant differences between the width and height of the lateral masses. However, axial measurements of Group 2 revealed a remarkable and significant length for screwing. Conclusion: In patients with cervical rib, directing lateral mass screw toward cervical rib conjoint can present a simple and reliable alternative method in C7 posterior stabilization process.
Keywords: C7; cervical rib; posterior stabilization; screwing